Legal opinion of leasing company management authorities in the form of joint stock company - Mentuh, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article deals with the management of the leasing company as a major leasing participant, without which the normal functioning of the leasing process, which can satisfy the needs for leasing services on a professional basis, and to which scientific interest has grown in business law. The basic theoretical and practical provisions concerning the governing bodies of the leasing company in the form of a joint stock company have been developed and formulated.It should be noted that despite the development of this problem, a number of issues remain unexplored and require a thorough definition and generalization. Therefore, this article is devoted to solving such problems as the governing bodies of a leasing company in the form of a joint stock company.Analyzing the current legislation, we can conclude that the vast majority of norms closely link the management of the company with the bodies of the company.According to the current legislation, the management of a joint-stock company (leasing company) is carried out by its governing bodies, which include: the general meeting as the supreme management body of the company, the supervisory board, which protects the rights of shareholders of the company and regulates the activities of the board, the executive body (board), which manages the current activities of the company, the audit committee.As a result, it can be noted that some of the problematic issues of the legal status of the governing bodies of a leasing company in the form of a joint-stock company, as the most common organizational and legal form of economic entities, are not fully resolved today due to insufficient regulation at the legislative level.